STUDI FENOMENOLOGI PERAN ORANG TUA SISWA DALAM MENERAPKAN PEMBELAJARAN DARING DI RUMAH SAAT PANDEMI COVID-19 - Muspik, Nasikhul; Septimar, Zahrah Maulidia (Nusantara Hasana Berdikari, 2022)
Online learning has been implemented for months, this strengthens the role of parents to be very important for the implementation of quality education. The role of parents is the responsibility of educating, nurturing and guiding their children to achieve certain goals, it is important to understand how the real role of parents in accompanying children during the COVID-19 pandemic. This study aims to determine the role of parents of elementary school students in implementing online learning at home during the covid-19 pandemic. This study uses qualitative research methods, qualitative phenomenology about three stages of phenomenology, namely intuitive, analytical, and descriptive stages. Data collection techniques were carried out by conducting interviews. The participants in this study were parents of elementary school students from grades 1 to 6 SD in Kronjo, Tangerang district. The results of interview analysis on eight participants, obtained four themes, namely: Long-Term Psychological Problems, The role of parents in online learning, Barriers experienced during online learning, Expectations for online learning. The role of parents is so important for children during online learning at home, where support greatly affects the quality of children in learning.